2002
DOI: 10.1046/j.1365-2141.2002.03751.x
|View full text |Cite
|
Sign up to set email alerts
|

Many αIIbβ3 autoepitopes in chronic immune thrombocytopenic purpura are localized to αIIb between amino acids L1 and Q459

Abstract: Summary. In chronic immune thrombocytopenic purpura (ITP), autoantibodies bind to platelet surface proteins, particularly a IIb , resulting in platelet destruction by the reticulo-endothelial system. In order to better localize the autoepitopes on a IIb , we studied the binding of antibodies to Chinese hamster ovary (CHO) cells expressing either a IIb b 3 or a IIb -a v b 3 chimaeras in which a segment of a IIb (either amino acids L1-Q459, L1-F223 or F223-Q459) was substituted for that portion of a v . We evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 12 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…13,15 In this study, we found that samples from 15 patients with primary ITP harbored PA anti-␣IIb␤3 Abs that mainly recognized the N-terminal half of the ␤-propeller domain (L1-W235) of ␣IIb. A systematic examination with human-mouse ␣IIb chimeras found 3 main recognition sites: (1) a conformational epitope composed of W1:1-2 and W2:3-4 loops, (2) a region containing the W1:2-3 loop, and (3) a region containing the W3:4-1 loop.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…13,15 In this study, we found that samples from 15 patients with primary ITP harbored PA anti-␣IIb␤3 Abs that mainly recognized the N-terminal half of the ␤-propeller domain (L1-W235) of ␣IIb. A systematic examination with human-mouse ␣IIb chimeras found 3 main recognition sites: (1) a conformational epitope composed of W1:1-2 and W2:3-4 loops, (2) a region containing the W1:2-3 loop, and (3) a region containing the W3:4-1 loop.…”
Section: Discussionmentioning
confidence: 97%
“…We and others previously reported that, in chronic ITP, PA anti-␣IIb␤3 Abs frequently bound to cation-dependent conformational antigens and did not react with ␣v␤3. [11][12][13] Those data suggested that, in primary ITP, the target epitopes of anti-␣IIb␤3 Abs may be localized mainly on ␣IIb; in contrast, in HIVassociated ITP, the target epitopes appeared to be localized to the 49-66 residues of ␤3. 14 Moreover, we previously reported that, in one-third of patients with ITP (11 of 34), PA anti-␣IIb␤3 Ab binding was markedly impaired against KO variant ␣IIb␤3, which had 2 amino acids inserted between residues 160 and 161 in the W3:4-1 loop of the ␤-propeller domain.…”
Section: Introductionmentioning
confidence: 89%
“…Subsequent studies have shown that autoantibodies particularly bind to the IIb subunit ( 117 , 118 ), or contradictory, the IIIa subunit of the dimer ( 119 ). Eventually, several investigators have demonstrated that specific portions of the protein are preferred autoepitopes in ITP, often near ligand binding sites ( 81 , 120 ). The vitronectin (α v β 3) receptor shares the β 3 integrin with GPIIb/IIIa and was shown to be an important autoantigen in ITP as well ( 121 ).…”
Section: Etiologymentioning
confidence: 99%
“…Integrin α v β 3 , which is broadly expressed on cancer and normal cells , is also a special platelet integrin antigen for GP‐specific IgG. Anti‐α v β 3 autoantibody was detected in chronic ITP patients , whereas its role in ITP is unknown.…”
Section: Introductionmentioning
confidence: 99%